Diastereoselective Synthesis of Vicinal Diamines by Aza‐Michael Addition of Chiral Phenethylamine to Nitroalkenes. Issue 34 (13th September 2018) - Ma, Chunying; Du, Jianxun; Liang, Yuhua; Feng, Wenhua
Abstract: An efficient aza‐Michael addition of ( R or S )‐ α ‐phenethylamine, a chiral nitrogen nucleophile to ( E )‐nitroalkenes2 a‐f permits the synthesis of vicinal diamines (or 1, 2‐di‐amine) after reduction of the 1, 4‐adducts3 a‐f (or3'a‐f ). The key adducts3 a‐f (or3'a‐f ) can be obtained in good yields (up to 78%) and excellent diastereoselectivities (up to > 98:2 dr (diastereomeric excess ratio)). In addition, this is one of the scarce examples where chiral phenethylamine and nitroalkenes have been used in catalyst‐free aza‐Michael additions. Our developed strategy opens an efficient entry to synthetic building blocks of vicinal diamines for natural products and drugs. Abstract : Here, we reported the synthesis of vicinal diamines employing readily available chiral phenethylamine as chiral auxiliary. Importantly, the key step of asymmetric aza ‐Michael addition can be carried out without additional catalyst, giving adducts in good yields and excellent diastereoselectivities, and this is one of the scarce examples where chiral phenethylamine and nitroalkenes have been used in catalyst‐free aza‐Michael additions.